LANDASAN FILOSOFIS ILMU EKONOMI PEMIKIRAN NASIRUDDIN AT-THUSI - Zamroni Jihad Fatikhatul Putra (Program Studi Ekonomi Syariah, 2024)
Economic philosophy is the basic principle of an economic system designed as a value-intensive scientific structure. Based on this economic philosophy, it can be directed to various financial tasks and goals that need to be achieved, such as economic principles, consumption goals, production, sales, economic development. One important contribution to the development of Islamic economic theory is the economic theory of Nasruddin at-Tusi. One of the main concepts discussed is social progress, where at-Tusi emphasizes the importance of equal distribution of wealth and resources in society. In addition, at-Tusi highlighted the importance of education in driving economic growth and social progress, with the premise that high educational standards can help foster creativity and accelerate innovation. For example, at-Tusi emphasized the importance of economic stability in creating an environment conducive to economic growth and social welfare, as well as hampering the state's ability to manage the economy in the interests of everyone. The purpose of this text is to provide an overview of Nasruddin at-Tusi's economic theory and its implications. This research uses qualitative research, so this research is a literature review. Namely the method of collecting library data, reading and taking notes as well as managing research materials. The data sources for this research were sought from various literature that describes Islamic philosophy, thought and civilization. The results of this research are to describe the philosophy and history of Nasiruddin At-Tusi's thought and civilization as well as a figure of renewal in the Islamic world.